1999
DOI: 10.1093/emboj/18.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Different functions for the thyroid hormone receptors TRalpha and TRbeta in the control of thyroid hormone production and post-natal development

Abstract: The biological activities of thyroid hormones are thought to be mediated by receptors generated by the TRα and TRβ loci. The existence of several receptor isoforms suggests that different functions are mediated by specific isoforms and raises the possibility of functional redundancies. We have inactivated both TRα and TRβ genes by homologous recombination in the mouse and compared the phenotypes of wild-type, and single and double mutant mice. We show by this method that the TRβ receptors are the most potent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
267
2
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(288 citation statements)
references
References 35 publications
14
267
2
5
Order By: Relevance
“…Deletion of both α and β TRs is compatible with life [36,37]. This contrasts with the complete TH deficiency in the athyreotic Pax8KO mouse that dies prior to weaning, unless rescued by TH.…”
Section: Combined Tr and Related Gene Deletionsmentioning
confidence: 90%
“…Deletion of both α and β TRs is compatible with life [36,37]. This contrasts with the complete TH deficiency in the athyreotic Pax8KO mouse that dies prior to weaning, unless rescued by TH.…”
Section: Combined Tr and Related Gene Deletionsmentioning
confidence: 90%
“…Indeed, it is an ecological shift that is characterized by modifications like neural maturation, intestine remodeling, or chondrogenesis that are reminiscent of similar events during amphibian metamorphosis. These modifications occur in correlation with a peak of TH production (both T 3 and T 4 ) (Hadj-Sahraoui et al, 2000), and were shown to be under the control of TH and TR (Flamant et al, 2002;Gauthier et al, 1999;Plateroti et al, 1999). Consequently, weaning should be viewed as homologous to classical metamorphosis even if the precise role of THs in controlling this event and the regulatory hierarchy controlled by these hormones should be better analyzed.…”
Section: Evolution Of Metamorphosis In Other Vertebrates: Why Direct mentioning
confidence: 99%
“…Effects of ligand and thyroid hormone receptor isoforms on hepatic gene expression profiles of thyroid hormone receptor knockout mice Thrb knockout mice have elevated thyroid-stimulating hormone (Tsh) and Th levels in their serum, thyroid gland hyperplasia, and a hearing defect (Forrest et al, 1996;Gauthier et al, 1999). Thra/Thrb double-knockout mice have also been generated and, surprisingly, survive, showing that the presence of Trs is not essential for viability (Gauthier et al, 1999;Gothe et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Thra/Thrb double-knockout mice have also been generated and, surprisingly, survive, showing that the presence of Trs is not essential for viability (Gauthier et al, 1999;Gothe et al, 1999). Although these mice show extreme Th resistance, they do not display the severe, lethal phenotype seen in mice that are congenitally deficient for Th (Flamant et al, 2002).…”
Section: Introductionmentioning
confidence: 99%